Recent Evidence of Hantavirus Circulation in the American Tropic (2014)
ABSTRACT: Hantaan virus was discovered in Korea during the 1970s while other similar viruses were later reported in Asia and Europe. There was no information about hantavirus human infection in the Americas until 1993 when an outbreak was described in the United States. This event promoted new studies to find hantaviruses in the Americas. At first, many studies were conducted in Brazil, Argentina, Chile, Uruguay and Paraguay, while other Latin American countries began to report the presence of these agents towards the end of the 20th century. More than 30 hantaviruses have been reported in the Western Hemisphere with more frequent cases registered in the southern cone (Argentina, Chile, Uruguay, Paraguay, Bolivia and Brazil). However there was an important outbreak in 2000 in Panama and some rare events have been described in Peru, Venezuela and French Guiana. Since hantaviruses have only recently emerged as a potential threat in the tropical zones of the Americas, this review compiles recent hantavirus reports in Central America, the Caribbean islands and the northern region of South America. These studies have generated the discovery of new hantaviruses and could help to anticipate the presentation of possible future outbreaks in the region.